Int Adv Otol 2023
DOI: 10.5152/iao.2023.22863
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Correlation Research of MicroRNA10a-5p and PIK3CA in Middle Ear Cholesteatoma

Abstract: Background: This study aimed to examine the roles of miR-10a-5p and phosphatidylinositol-4,5-bisphosphonate 3-kinase catalytic subunit α in the pathogenesis of middle ear cholesteatoma. Methods: We enrolled 27 patients with middle ear cholesteatoma and collected samples of intraoperative cholesteatoma and normal posterior ear skin tissues. The mRNA expression levels of miR-10a-5p and PIK3CA were detected using real-time quantitative polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In total, 118 articles were retrieved through the database search. After applying the search strategy described above, a total of 18 articles were identified that met all inclusion criteria [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. A flow diagram of the detailed study selection process is presented in Figure 1.…”
Section: Search Results Study Characteristics and Study Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 118 articles were retrieved through the database search. After applying the search strategy described above, a total of 18 articles were identified that met all inclusion criteria [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. A flow diagram of the detailed study selection process is presented in Figure 1.…”
Section: Search Results Study Characteristics and Study Qualitymentioning
confidence: 99%
“…In another study [41], middle ear cholesteatoma tissues showed significantly decreased miR-10a-5p expression and increased PIK3CA expression compared to normal posterior ear skin tissues (p < 0.05). The results of target gene prediction revealed that PIK3CA may be an miR-10a-5p target gene.…”
Section: Microrna-10a-5pmentioning
confidence: 90%
See 1 more Smart Citation